Dalpiciclib plus aromatase inhibitor versus neoadjuvant chemotherapy for ER-positive, HER2-negative breast cancer - Wang, Haoqi; Zhang, Guoyu; Gao, Wei; Li, Sainan; Yang, Shan; Zhang, Xi; Wang, Jiaxing; Li, Chunxiao; Gao, Shan; Geng, Cuizhi (Frontiers in Oncology, 2025)
BackgroundThe combination of cyclin-dependent kinases 4 and 6 inhibitors (CDK4/6i) with endocrine therapy (ET) has emerged as an effective alternative to neoadjuvant chemotherapy (NCT) for patients with hormone receptor-positive (HR+) and human epidermal growth factor receptor 2 (HER2) -negative breast cancer (BC). This single-center study retrospectively evaluated the efficacy and safety of dalpiciclib combined with an aromatase inhibitor (AI) compared to NCT.MethodsThe clinicopathological data and treatment details of patients with HR+ HER2 negative BC who underwent either neoadjuvant endocrine therapy (NET) or NCT were collected from the Fourth Hospital of Hebei Medical University. The primary endpoint of the study was the Residual Cancer Burden (RCB), while secondary endpoints included breast pathological complete response (bpCR), clinical response rates (ORR), proliferation markers, and safety profiles.ResultsBetween May 2022 and June 2023, a total of 36 patients were treated with dalpiciclib plus AI, while 137 patients received NCT for the final analysis. Prior to propensity score matching (PSM), the rates of RCB 0 were 0% in the NET group and 7.3% in the NCT group (p=0.205). The rates of bpCR were 2.8% for the NET group and 13.1% for the NCT group (p=0.142). The ORR was comparable between the two groups (p=0.397), as were the rates of BCS (p=0.608). Both treatment groups demonstrated significant reductions in Ki-67 levels, although the extent of reduction was similar (p=0.174). Notably, a Ki-67 level of ≤ 10% post-treatment was more prevalent in the NET group (p<0.0001). Only two patients in the NET group achieved a Preoperative Endocrine Prognostic Index (PEPI) 0 score. The incidence of grade 3–4 toxicities was significantly higher in the NCT group compared to the NET group (p<0.05). Following PSM, patients treated with dalpiciclib plus AI exhibited comparable clinical responses and a safety advantage relative to those receiving NCT.ConclusionThis study indicates that the combination of dalpiciclib and AI elicits comparable responses and demonstrates improved safety profiles when compared to NCT in patients with HR+ HER2 negative breast tumors. Furthermore, RCB and pCR may not serve as optimal endpoints for evaluating the efficacy of CDK4/6i-based NET.